Trade as a cultural identity aspect in a city. A case study on Catania - Caterina Cirelli; Leonardo Mercatanti; Carmelo Maria Porto; Elena Di Blasi; Enrico Nicosia (European Regional Science Association (ERSA), 2004)
In the present-day post-industrial society and in a globalised economy there is a strong tendency towards standardization and homologation. If we consider one of the most traditional urban functions - the commercial one - analysing what is happening in the centre of the cities of all the developed countries of the world, we notice a process of standardization regarding the offer, both in the sense of the single articles sold and in the sense of the commercial area in all its complexity (uniformity of the showcases for the exposure, diminution of the historical shops with sale of distinctive articles, diffusion of the branches of national and international chains and the phenomenon of franchising). Therefore, the central areas of our cities tend to be more and more alike. Obviously this is fruit of a more complex process, that is concretized in the tendency towards the diversification of the distributive network through the rapid diffusion of hypermarkets and commercial centres in the outskirts of cities and in the changed behaviour of the consumers, more and more directed to American styles of consumption. What kind of role will the more traditional commercial structures that characterize the Italian historical centres have in the future? Despite the fact that these last ones are, at the moment, under considerable pressure that pushes towards a more radical change, there is the possibility however that the particular "commercial landscape" that characterizes them could itself become a new model of development capable of promoting the urban culture, close to the functionalistic model, currently in expansion, totally directed towards the peripheral spaces. Catania is a city where we find, to a great extent, the evolutionary characteristics of the southern urban system, but in which we find even more the changes and the tendencies present in the cities of the more developed regions when processes of decentralization of economic activities, residential activities and of the social structures are outlined. The commercial patrimony of Catania, besides the cultural one, represents one of the pivots on which the identity of the city is based. It represents a resource for the development of the town and a stimulation of tourism. This research investigates the solidity and the potentialities of traditional commerce in the central areas of the city of Catania in relation to the dynamics of development of the external commercial centres.
Keywords: 330